Marco Polo and the discovery of the world - Larner, John (Yale University Press, 1999)
After many years in Asia, Marco Polo wrote one of the most influential books of the past millennium. No mere travel account, Polo's Book is a work that played a key role in the development of European overseas expansion. In this book, historian John Larner explores for the first time the full range and influence of Polo's Book on the history of geography and exploration. Larner assesses the findings of modern scholarship and offers an original account of Marco Polo and his family, of how and why the Book came into being, and of its reception over the centuries.